Implementasi Pembelajaran Al-Qur’an Hadits di MTs Al-Fathimiyyah Karawang - nabilatul fauziah, debibik (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2025)
The subject of Al-Qur'an Hadith is a subject that must be followed by students at MTS Al-Fathimiyyah Karawang. Teachers of the Qur'an Hadith subject in this school still use conventional methods in learning, therefore this study aims to find out the implementation of learning the Qur'an hadith and its supporting and inhibiting factors. The method used in this study is a descriptive qualitative method. Data collection techniques are carried out through observation, interviews and documentation. The primary source of data in this study is the results of interviews with sources, while the secondary source is obtained from journal articles that discuss the learning of the Qur'an Hadith. The data was analyzed by data reduction methods, data presentation and conclusion drawn. The results of the study found that the learning of the Qur'an Hadith at MTS Al-Fathimiyah still uses conventional methods such as lectures, memorization, discussion and demonstration methods. The learning media used by teachers are print media and electronic media. Supporting factors in learning are the existence of a clear and structured curriculum, the ability of competent teachers in the field of Al-Qur'an Hadith, the support of parents and the surrounding environment, and social activities initiated by the school. The inhibiting factors are student indiscipline and laziness, limited learning time, and inadequate infrastructure facilities at school.